Maternal depression and child psychopathology among Attendees at a Child Neuropsychiatric Clinic in Abeokuta, Nigeria: a cross sectional study. Issue 1 (December 2016) - Okewole, Adeniran; Adewuya, Abiodun; Ajuwon, Ademola; Bella-Awusah, Tolulope; Omigbodun, Olayinka
Abstract Background Children with recognized, diagnosable mental and neurological disorders are in addition prone to emotional and behavioral problems which transcend their specific diagnostic labels. In accessing care, these children are almost invariably accompanied by caregivers (usually mothers) who may also have mental health problems, notably depression. The relationship between child and maternal psychopathology has however not been sufficiently researched especially in low and middle income countries. Methods Mothers (n = 100) of children receiving care at the Child and Adolescent Clinic of a Neuropsychiatric Hospital in Abeokuta, Nigeria took part in the study. To each consenting mother was administered a sociodemographic questionnaire and the Patient Health Questionnaire, while information regarding their children (n = 100) was obtained using the Strengths and Difficulties Questionnaire. Data analysis was done with the Statistical Package for Social Sciences (SPSS) version 16. Results The mean ages of the mothers and children were 40.4 years (SD 4.7) and 11.6 years (SD 4.1), respectively. Among the children, 63 % had a main diagnosis of seizure disorder. Regardless of main diagnosis, 40 % of all the children had a comorbid diagnosis. Among the mothers, 23 % had major depressive disorder. A quarter (25 %) of the children had abnormal total SDQ scores. A diagnosis of major depressive disorder in mothers was associated with poor total SDQ scores and poor scores in all SDQ domains except the emotional domain for the children. Major depressive disorder among the mothers was associated with not being married (p = 0.004; OR = 0.142, 95 % CI 0.037–0.546) and longer duration of the child's illness (p = 0.039, OR = 1.165, 95 % CI 1.007–1.346). Conclusion The study showed notable rates of depressive illness among mothers of children with neuropsychiatric disorders. Marked rates of emotional and behavioral disorders were also found among the children. Associations were found between maternal and child psychopathology. Mothers of children with neuropsychiatric disorders should be screened for depressive illness.